The Future of Creative Expression Through Professional Artistic Education: Artificial Intelligence and Human Art - Cota Rivera, Elia Ivette; González Correa, Martha Elena (Emerging Trends in Education, 2025)
Academics from higher education institutions that offer programs in creative fields such as Visual Arts, Plastic Arts, Audiovisual Media, Animation and Visual Effects, Architecture, Cinematography, Communication, and other related areas face the enormous responsibility of developing themselves and preparing to tackle the challenges of this technological transformation. It is imperative to critically analyze how artificial intelligence and new technologies can enrich and transform the field of art. At the same time, it is essential to examine the risks and difficulties associated with the use of new technologies. This presentation directs the reflection toward the revaluation of human creativity and artistic expression through the study of algorithms that imitate human creativity employed in artificial intelligence. To this end, a systematic literature review is conducted to identify the differences that exist between human creativity and the training of AI algorithms. We believe that academia should serve as a space for reflection on the impact of artificial intelligence on creative work. Likewise, the new generations of professionals must possess elements that enable them to recognize, appreciate, and defend the intrinsic value of their creative work, which is irreplaceable. An analysis of the ethical consequences of using generative artificial intelligence in the creative field will trigger relevant discussions about the rights of artists and the value of original artwork, guiding actions toward regulatory frameworks that protect original creations.